2015
DOI: 10.4028/www.scientific.net/amm.773-774.134
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Effect of Orientation Fabric on Mechanical Energy Absorption Natural Fibres Reinforced Composites

Abstract: This paper presents the combination technique in developing the woven kenaf fiber that is used as a new method to improve energy absorption performance. This method focuses on the effect energy absorption of angle orientation. Due to the low density, natural fiber such as kenaf fiber provides comparatively good mechanical properties. Thus, natural fibers have high potential for better reinforcement in light weight structures on automotive applications. Total force, total energy, and energy absorption of natura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Recently, several authors have studied the influence of layer orientation on the ballistic performance and energy absorption. [76][77][78][79] In their research, Wang et al investigated the ballistic impact resistance of multilayered woven aramid layers depending on the layers' orientation. They proved that the ply orientations highly affect the capacity of energy absorption of the multilayered soft panel.…”
Section: Soft Mbsmentioning
confidence: 99%
“…Recently, several authors have studied the influence of layer orientation on the ballistic performance and energy absorption. [76][77][78][79] In their research, Wang et al investigated the ballistic impact resistance of multilayered woven aramid layers depending on the layers' orientation. They proved that the ply orientations highly affect the capacity of energy absorption of the multilayered soft panel.…”
Section: Soft Mbsmentioning
confidence: 99%
“…In the recent years, industries actively attempt to reduce the dependence on petroleum based fuels and products due to the increasing environmental consciousness. This leads to the need to investigate environmentally friendly and sustainable materials to replace the existing synthetic fibres [1][2][3]. The increase of production and usage of plastics in every sector of our daily life lead to massive plastic wastes.…”
Section: Introductionmentioning
confidence: 99%
“…However, their expensive price limits their widespread use. Currently, the most viable way toward eco-friendly composites is the use of natural fibres as reinforcement [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Hybridizing metallic tubes with natural fibres are very difficult to find. There are several papers conducted to investigate the crushing responses can be found [12][13][14][15][16][17][18][19]. Most of these papers found that natural fibre capable to increase the capacity of energy absorption.…”
Section: Introductionmentioning
confidence: 99%